Understanding emotion processing in schizophrenia - Gur, R. C.; Keutmann, M. K.; Gur, R. E. (Die Psychiatrie, 2010)
Impaired emotional functioning is a prominent feature of schizophrenia. Although positive symptoms have traditionally attracted more attention and targeted treatment, negative symptoms, including flat affect, are increasingly recognized as the more debilitating and resistant to intervention. We describe studies examining affect processing in schizophrenia, focusing on facial affect with initial findings in vocal affect, or prosody. Deficits in schizophrenia are pronounced, and studies with functional neuroimaging indicate that the neural substrates for these deficits center on the amygdala and its projections. The abnormalities are highly correlated with symptom severity and functional outcome. While there is quite extensive work on affect recognition abnormalities, deficits have also been documented in the ability to express affect on the face and in voice, and perhaps to a lesser extent in the experience of emotion. These abnormalities can be better studied when methods for quantitative analysis of emotional expression are available. Recognizing the existence of such deficits and their neural substrates will lead to improved approaches to pharmacological and behavioral treatment.
Keywords: Emotion; schizophrenia; functional neuroimaging; flat affect; negative symptoms; amygdala